2017
DOI: 10.1038/s41598-017-02327-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of extracellular glycerophosphodiesterases in Pseudomonas and their role in soil organic phosphorus remineralisation

Abstract: In soils, phosphorus (P) exists in numerous organic and inorganic forms. However, plants can only acquire inorganic orthophosphate (Pi), meaning global crop production is frequently limited by P availability. To overcome this problem, rock phosphate fertilisers are heavily applied, often with negative environmental and socio-economic consequences. The organic P fraction of soil contains phospholipids that are rapidly degraded resulting in the release of bioavailable Pi. However, the mechanisms behind this proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 51 publications
0
30
0
Order By: Relevance
“…The ugp genes were principally transcribed by members of the Order Rhizobiales (Class alpha-Proteobacteria), potentially replacing Pi transport as a phosphorus acquisition mechanism (Figure 2B). Plant exudates or membrane phospholipids are possible sources of G3P in soils (Ding et al, 2012; Collins et al, 2014; Lidbury et al, 2017). The glpQ gene product can cleave these compounds, releasing G3P and triggering activation of the ugp transporter genes (Brzoska and Boos, 1988).…”
Section: Resultsmentioning
confidence: 99%
“…The ugp genes were principally transcribed by members of the Order Rhizobiales (Class alpha-Proteobacteria), potentially replacing Pi transport as a phosphorus acquisition mechanism (Figure 2B). Plant exudates or membrane phospholipids are possible sources of G3P in soils (Ding et al, 2012; Collins et al, 2014; Lidbury et al, 2017). The glpQ gene product can cleave these compounds, releasing G3P and triggering activation of the ugp transporter genes (Brzoska and Boos, 1988).…”
Section: Resultsmentioning
confidence: 99%
“…An enhanced secretion of certain enzymes related to phosphate uptake was shown to be triggered by low phosphate conditions. A subsequent study proved that even co‐cultured bacteria could benefit from this extracellularly occurring metabolism (Lidbury et al ., ). Although this example is related to the nutrient provision of co‐formulated partners, it might be transferred to the provision of desiccation protectants.…”
Section: Desiccation Damage and Protective Strategiesmentioning
confidence: 97%
“…This difference suggests that bacteria associated with stylo prefer Po mineralization as an important strategy for P acquisition. glpQ encodes phosphodiesterase catalyzing the hydrolysis of the phosphorus diester (Lidbury et al, 2017). Canellas et al (2004) indicated that legumes increased soil phosphorus diester content more effectively than grass.…”
Section: Gene Abundance Involved In Soil P Cycling Affected By Legumementioning
confidence: 99%